KARAKTERISTIK PROGRAM PEMBERDAYAAN MUSTAHIK OLEH LEMBAGA AMIL ZAKAT NASIONAL DI INDONESIA - Ernawati Ernawati (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
This study aims to investigate the characteristics of empowerment mustahik by Lembaga Amil Zakat Nasional (LAZNAS). The sample consisted of 13 LAZNAS. Data obtained through the publication of directories on line LAZNAS. Characteristics of the empowerment program assessed in six dimensions: type of aid, the target group, target area, target age, gender and agriculture-based . The data were analyzed descriptively with tabulation, percentages and charts. The results showed that the type of the empowerment program conducted by LAZNAS in Indonesia consists of: financial aid, assistance tools, training and mentoring, as well as other type such as reinforcement, the legality of operations and strengthening the network of business. However, not all LAZNAS adopt this type of aid. The whole LAZNAS have targeted both mustahik empowering individuals and groups. LAZNAS also generally have a Village Project. On the other hand, LAZNAS in general has given space to the development of community enterprises in the agricultural sector. But lack of attention at a young age and female mustahik. Only three LAZNAS that provides direct attention to the younger group; and one for woman empowerment.